Pollution in Africa : a new toxic waste colonialism? An assessment of compliance of the Bamako Convention in Cote d’Ivoire - Tamirat, Imeru (University of Pretoria, 2010)
A Dissertation submitted to the Faculty of Law University of Pretoria, in partial fulfilment of the requirements for the degree Masters of Law (LLM in Human Rights and Democratisation in Africa). Prepared under the supervision of Mr Imeru Tamirat, Faculty of Law, Addis Ababa University